Security and Compliance in Integration Architectures: A Framework for Modern Enterprises - Padmanabham, Sapthagiri (International Journal of Computing and Engineering, 2025)
This article addresses the critical security and compliance challenges in modern integration architectures, which have grown increasingly complex with the adoption hybrid cloud environments, SaaS applications, and IoT devices. The integration layer has become a crucial connector between disparate systems and a significant security frontier, often inadequately protected. By examining the evolution of integration patterns from point-to-point connections to cloud-based platforms, the article identifies key threat vectors including API vulnerabilities, middleware weaknesses, and internal threats. A comprehensive framework based on Zero Trust principles is presented, encompassing secure API design, data protection mechanisms, and compliance-ready architecture. Through detailed case studies across financial services, healthcare, and retail sectors, the article demonstrates practical implementation strategies for maintaining security and regulatory compliance. The multi-layered framework provides organizations with actionable guidance to establish integration architectures that balance business agility with robust security postures in an increasingly complex digital landscape.